A Review on Landfill Leachate Treatment Technologies: Comparative Analysis of Methods and Process Innovation - Rongcheng Xiang; Wugan Wei; Tianhong Mei; Zihan Wei; Xiaorui Yang; Jinhua Liang; Jianliang Zhu (Applied Sciences)
Landfill leachate, characterized by its high concentration of organic matter (high COD), elevated ammonia and nitrogen levels, high salinity, and toxicity, poses a significant challenge for environmental pollution control. In recent years, extensive research efforts have been dedicated to treating landfill leachate, resulting in the implementation of various engineering technologies. However, with the advancement of analytical techniques, an increasing number of emerging contaminants (ECs) have been detected in landfill leachate. These pollutants pose potential environmental and health risks, yet traditional wastewater treatment technologies struggle to effectively remove them, necessitating innovative upgrades to existing methods. This paper reviews the current research status of landfill leachate treatment technologies, compares the advantages and disadvantages of various techniques, and emphasizes the importance of technological innovation in treatment processes.